2017
DOI: 10.1089/jpm.2016.0323
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Delirium in Corticosteroid-Treated Patients with Advanced Cancer: An Exploratory, Multicenter, Prospective, Observational Study

Abstract: Delirium in corticosteroid-treated advanced cancer patients may be predicted by PS, drowsiness, and concurrent opioid use. Larger prospective studies are needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(65 citation statements)
references
References 33 publications
0
65
0
Order By: Relevance
“…35 Matsuo et al's naturalistic cohort study focused on CAH in patients with advanced cancer who had been prescribed steroids, revealing an association between lower received volume of CAH and the development of delirium (p=0.034). 36 Yamaguchi et al found worse agitation (p=0.025) and a higher prevalence of agitated delirium (p=0.009) in patients with advanced abdominal malignancies receiving less CAH. 37 Although participants in the latter two studies were mostly in the last weeks, rather than last days, of life, (and thus excluded from this review), together with the findings from the feasibility study included in this review, 20 there is a suggestion that CAH may reduce the incidence or severity of delirium as oral intake declines.…”
Section: Discussionmentioning
confidence: 94%
“…35 Matsuo et al's naturalistic cohort study focused on CAH in patients with advanced cancer who had been prescribed steroids, revealing an association between lower received volume of CAH and the development of delirium (p=0.034). 36 Yamaguchi et al found worse agitation (p=0.025) and a higher prevalence of agitated delirium (p=0.009) in patients with advanced abdominal malignancies receiving less CAH. 37 Although participants in the latter two studies were mostly in the last weeks, rather than last days, of life, (and thus excluded from this review), together with the findings from the feasibility study included in this review, 20 there is a suggestion that CAH may reduce the incidence or severity of delirium as oral intake declines.…”
Section: Discussionmentioning
confidence: 94%
“…The characteristics of the nine included studies were presented in Table 1 (9,10,(15)(16)(17)(18)(19)(20)(21). Among these studies, three were case-control studies (9,19,20), and five were cohort studies (10,(15)(16)(17)(18).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The characteristics of the nine included studies were presented in Table 1 (9,10,(15)(16)(17)(18)(19)(20)(21). Among these studies, three were case-control studies (9,19,20), and five were cohort studies (10,(15)(16)(17)(18). The studies involved 4,939 subjects (899 delirium cases and 4,040 non-delirious controls) from five countries.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations